Mood states according to sociodemographic variables in the Peruvian population - Jose Calizaya-Lopez; Yaneth Aleman-Vilca; Merly Lazo-Manrique; Juan Manuel Coaquira-Mamani; Magnolia Susana Sierra-Delgado; Omar Emilio Trujillo-Zeballos; Ana Barreda-Coaquira; Irving Juan Manuel Coaquira-Ramon; Renzo Rimaneth Rivero-Fernandez; Claudia M. Salas-Carazas (Environment and Social Psychology, 2025)
Mood states represent a central dimension of psychological well-being, influenced by multiple factors, including sociodemographic variables. However, in the Peruvian context, there is still no extensive empirical evidence that explores how these variables modulate emotional responses at different stages of the life cycle. Moods were analyzed according to sociodemographic variables in a representative sample of the Peruvian population. A quantitative, non-experimental and cross-sectional design was applied; 2283 people participated distributed according to population groups (adolescents, youth, adults and older adults). A validated scale was used to assess the child’s condition. Data was analysed with non-parametric tests (absence of normal distribution in the data). High and medium levels were found in the dimensions of mood, significant differences were found in the dimensions of anxiety, depression, joy and hostility according to sociodemographic variables. Women and divorced/widowed people reported higher levels of anxiety and depression. Participants with higher levels of education, higher incomes, and residents of urbanized areas showed higher levels of joy. Adolescents, women, and people with higher education had higher scores in hostility. It is concluded that moods are influenced by specific sociodemographic characteristics, evidencing the need for differentiated interventions according to population profile, implementing community mental health strategies, especially in vulnerable contexts.